2004
DOI: 10.1002/j.1556-6678.2004.tb00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Vicarious Trauma: What Counselors Should Know When Working With Trauma Survivors

Abstract: Counselors in all settings work with clients who are survivors of trauma. Vicarious trauma, or counselors developing trauma reactions secondary to exposure to clients' traumatic experiences, is not uncommon. The purpose of this article is to describe vicarious trauma and summarize the recent research literature related to this construct. The Constructivist Self-Development Theory (CSDT) is applied to vicarious trauma, and the implications CSDT has for counselors in preventing and managing vicarious trauma are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
212
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(227 citation statements)
references
References 16 publications
2
212
0
13
Order By: Relevance
“…In regards to forensic interviewing specifically, the participants reported a mean of 5.5 years of experience, with a range of 0.5 to 18 years. All of the participants reported that they had experienced vicarious trauma symptoms, which were indicated by physical symptoms, emotional symptoms, behavioral symptoms, work related issues, interpersonal problems, and/or professional efficacy such as a decrease in concern and esteem for clients (Baird & Jenkins, 2003) [11,[24][25][26][27][28]; Perry, 2003; [29]. Researchers did not inquire about historical mental health and/or trauma of participants prior to the commencement of the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In regards to forensic interviewing specifically, the participants reported a mean of 5.5 years of experience, with a range of 0.5 to 18 years. All of the participants reported that they had experienced vicarious trauma symptoms, which were indicated by physical symptoms, emotional symptoms, behavioral symptoms, work related issues, interpersonal problems, and/or professional efficacy such as a decrease in concern and esteem for clients (Baird & Jenkins, 2003) [11,[24][25][26][27][28]; Perry, 2003; [29]. Researchers did not inquire about historical mental health and/or trauma of participants prior to the commencement of the study.…”
Section: Methodsmentioning
confidence: 99%
“…One important occupational construct associated with job stress and turnover is vicarious trauma [6,15]. Theorists differentiate vicarious trauma from other processes related to professional's experiences of their client's trauma (e.g., compassion fatigue, secondary traumatic stress) in that vicarious trauma is characterized by a shift in intrapersonal processes (i.e., changes in trust, feelings of control, issues of intimacy, esteem needs, safety concerns, and intrusive imagery) as a result of working with traumatized clients [11]. Unlike compassion fatigue (a reduced capacity or interest in being empathic or bearing the suffering of clients which is a consequence of knowing about a traumatizing event experienced by a person; [16] or secondary traumatic stress (an acute stress reaction to a secondary traumatic event which mimics post-traumatic stress disorder; PTSD) [8,9,17] vicarious trauma results in a cognitive shift which involves "profound changes in the core aspects of the professional's self and… may involve disruptions in the cognitive schemas" of helping professionals' "identity, memory system, and belief system" [11].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Trauma education also has relevance to understanding and addressing work-related stress, burnout, and organizational trauma (Dane, 2000;Trippany, Kress, & Wilcoxon, 2004). Some research findings suggest that trauma education may be of even greater relevance to preparing bachelor's level social workers for practice.…”
Section: Principle 9: Self-carementioning
confidence: 99%